HCF1 and OCT2 Cooperate with EBNA1 To Enhance OriP-Dependent Transcription and Episome Maintenance of Latent Epstein-Barr Virus - Dheekollu, Jayaraju (J Virol, 2016)
Epstein-Barr virus (EBV) establishes latent infections as multicopy episomes with complex patterns of viral gene transcription and chromatin structure. The EBV origin of plasmid replication (OriP) has been implicated as a critical control element for viral transcription, as well as viral DNA replication and episome maintenance. Here, we examine cellular factors that bind OriP and regulate histone modification, transcription regulation, and episome maintenance. We found that OriP is enriched for histone H3 lysine 4 (H3K4) methylation in multiple cell types and latency types. Host cell factor 1 (HCF1), a component of the mixed-lineage leukemia (MLL) histone methyltransferase complex, and transcription factor OCT2 (octamer-binding transcription factor 2) bound cooperatively with EBNA1 (Epstein-Barr virus nuclear antigen 1) at OriP. Depletion of OCT2 or HCF1 deregulated latency transcription and histone modifications at OriP, as well as the OriP-regulated latency type-dependent C promoter (Cp) and Q promoter (Qp). HCF1 depletion led to a loss of histone H3K4me3 (trimethylation of histone H3 at lysine 4) and H3 acetylation at Cp in type III latency and Qp in type I latency, as well as an increase in heterochromatic H3K9me3 at these sites. HCF1 depletion resulted in the loss of EBV episomes from Burkitt's lymphoma cells with type I latency and reactivation from lymphoblastoid cells (LCLs) with type III latency. These findings indicate that HCF1 and OCT2 function at OriP to regulate viral transcription, histone modifications, and episome maintenance. As HCF1 is best known for its function in herpes simplex virus 1 (HSV-1) immediate early gene transcription, our findings suggest that EBV latency transcription shares unexpected features with HSV gene regulation. IMPORTANCE EBV latency is associated with several human cancers. Viral latent cycle gene expression is regulated by the epigenetic control of the OriP enhancer region. Here, we show that cellular factors OCT2 and HCF1 bind OriP in association with EBNA1 to maintain elevated histone H3K4me3 and transcriptional enhancer function. HCF1 is known as a transcriptional coactivator of herpes simplex virus (HSV) immediate early (IE) transcription, suggesting that OriP enhancer shares aspects of HSV IE transcription control.